Rise and Decline of the Coffee Industry in 19th-Century Batangas: Causes and Consequences - Belamide, Aidel Paul G (Philippine Social Sciences Review; PSSR Vol. 72 No. 2 2020, Ed. Jorge V. Tigno, 2024)
Coffee rose from an almost unknown plant in the mid-18th century to one of the top high-value exports in the Philippines by the end of the 19th century. The industry that coffee produced within a century led to structural changes that altered the lives and communities of farmers and traders. This research attempts to provide a social history of the coffee industry in Southern Tagalog during the Spanish colonial period. It traces the origin, growth, and decline of the coffee industry in Batangas within the context of the changing political economy and ecology and tracks the concomitant socio-economic transformation in the province during the 19th century. Batangas was the coffee center in the Spanish colonial Philippines. Archival records and key historical studies were the primary sources of data.